REBT-Based Group Counseling for Self-Efficacy Enhancement in At-Risk Adolescents: A Quasi-Experimental Study in a Social Care Institution - Meti Puspitasari; Nisa Rachmah Nur Anganthi (Kajian Psikologi dan Kesehatan Mental, 2025)
Purpose: Adolescent beneficiaries of social care institutions often experience low self-efficacy due to trauma, family dysfunction, limited educational opportunities, and social stigma. This study examined the effectiveness of Rational Emotive Behavior Therapy (REBT)-based group counseling in improving self-efficacy among female adolescents at Panti Pelayanan Sosial Wanita (PPSW) Wanodyatama, Surakarta.Research Methodology: A quasi-experimental one-group pretest–posttest design was employed. Seven female adolescents aged 15–18 years with low-to-moderate self-efficacy levels were selected through purposive sampling. The intervention consisted of six structured REBT group counseling sessions delivered over three weeks, focusing on identifying and disputing irrational beliefs, fostering rational thinking, and strengthening adaptive behavior. Self-efficacy was measured using the General SelfEfficacy Scale (GSE), while observation and interviews provided supporting data. The Wilcoxon Signed Rank Test was used for analysis.Results: Self-efficacy scores increased from a mean of 19.71 at pretest to 28.86 at posttest, representing a 46.4% improvement. All participants demonstrated positive gains. Statistical analysis indicated a significant difference between pretest and posttest scores (Z = ?2.375, p = .018), with a large effect size (r = 0.898). Conclusions: REBT-based group counseling effectively improves self-efficacy among at-risk female adolescents in social care settings.Limitations: The study was limited by its small sample size, lack of a control group, and short intervention period.Contributions: The findings provide evidence supporting REBT group counseling as a practical intervention model for psychosocial empowerment programs in social care institutions.